Volume Angkutan Sedimen Dipengaruhi oleh Kecepatan Aliran (Kajian : Laboratorium) - Adinegara, Subary (MEDIA KOMUNIKASI TEKNIK SIPIL, 2005)
The volume of sediment transport in a river can be predicted by varions formula such as Meyer-Peter, Schocklitsch, Kalinske and Enstein. The application of those formular result in high naviation raising the questions of which formula is appropriate. This paper presents the evaluation of an appropriate sediment transport formula by comparing the result of laboratory experiment with the analytical result. It is found that for the range of data analysed, the Schocklitsch formula is more appropriate.Keywords: sediment transport, laboratory experimentPermalink: http://ejournal.undip.ac.id/index.php/mkts/article/view/3913[How to cite: Adinegara, S., 2005, Volume Angkutan SedimenÂ  Dipengaruhi oleh Kecepatan Aliran (Kajian : Laboratorium), Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 2, pp. 94-105]